Predicting Environmental Leadership Based on Personality and Its Construct Validity - Putrawan, Made (International Journal of Engineering and Technology, 2018)
Environmental issues nowdays have been an interesting topic discussed by any institutions in most countries. One of them is concern with environmental management determined by leadership. How environmental leadership (EL) be explained and predicted by personality (EP) and how their construct validity are research problems. A survey method has been applied by involvingÂ 237 employees of government official in environmental sector, in Jakarta city, as sample selected randomly. Two instruments have been developed; Environmental Leadership (EL) and Environmental Personality (EP). Its reliability was respectively .991 (EL) and .907(EP). Data has been analyzed by regression & correlation analysis and confirmatory factor analysis (CFA) as well. Research results revealed that ony two factors of big-five personality have a positive and significant contribution toward environmental leadership, Â extraversion and openness to the experience, even though it has been applied by fourth-order correlation, it was only emotional stability did not support it. Considering to factor analysis results, either of environmental personality or environmental leadership, has a high construct validity since all factors loading did confirm theoretical dimensions empirically. There is no doubt that both instruments could be taken into consideration to be implemented scientifically, concern withÂ environmental research.